A qualitative study of seven simulation models for tendon repairs. (October 2021) - Vinnicombe, Zak; Asher, Christian M.; Super, Jonathan; Bystrzonowski, Nicola; Katsarma, Eufrossyni
Seven models for tendon repair simulation (urinary catheter, liquorice, fishing lure, dental rolls, drinking straw, silicone sealant and the authors' modification of silicone sealant with Micropore™ tape) were assessed for their performance in a number of domains. The silicone sealant and surgical tape model scored highest overall and for each individual domain. This was significantly higher than all other models with the exception of the silicone sealant alone. The lowest scoring model was the drinking straw model.